OPTIMALISASI VISIBILITAS MENGGUNAKAN SPACE SYNTAX: STUDI KASUS GEDUNG GALERI NUSANTARA SEMARANG - Alifiano Rezka Adi; Muhammad Rizqi (Nature : National Academic Journal of Architecture, 2023)
During an art and architecture exhibition, the gallery building becomes a crowded space where the interior quality can influence visitors visual comfort. High density caused by an unstructured layout can lead to a low quality visibility. Galeri Nusantara was used as a case study in this research by focusing on visibility optimization using a space syntax approach with Depthmap application. The analysis was carried out based on the VGA (visibility graph analysis) map on the visual integration [HH] parameter. Modeling was made in several layouts that were possible to implement. The results show that the distribution of the highest and lowest visibility levels for each layout is relatively similar. Small differences occur when there is a change from pustek to panel board arrangement. The quality of visibility is reflected in the visibility area coverage and the R2 value which describes the relationship between connectivity and visual integration. The VGA map shows that the use of pustek provides optimal visibility as indicated by the high R2 value. The low R2 values are more common in panel board arrangements because there are areas with low visibility within a fairly wide coverage area. It results in overall low R2 value in the gallery.